Peningkatan Hasil Belajar Mata Kuliah Instalasi Listrik Melalui Pendekatan Learning Cycle Five “E” (LC 5 E) - Zamtinah, Zamtinah; Hafidz, Hafidz (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objective of this study was to improve the students’ motivation and achievement in the course of Electrical Installation through the 5 E learning cycle (5 E LC) at the Department of Electrical Engineering Education, Faculty of Engineering, Yogyakarta State University. The approach used in this study was the 5 stages of the 5 E learning cycle consists of Engagement, Exploration, Explain, Extend, and Evaluation. This  study is categorised as Classroom Action Research (CAR). It referred to the model of CAR offered by Kemmis and Taggart. The data was collected using documentation, questionnaires, observation and tests. The data was analysed descriptively. The results of the study showed the 5 E learning cycle could improve the students’ achievement, learning activities, and learning motivation. The mean score of learning achievement was 79. It  was higher compared to the minimum target that was 60. The improvement of learning activities in the first  cycle, second cycle and third cycle were 1.25, 2.42, and 2.92 respectively. The improvement of learning motivation in the first cycle, second cycle and third cycle were 2.5, 2.8, and 3.2 respectively.